Assessment of stress transfer in laminated structural power composites produced with mechanically-connected electric double-layer capacitors. (8th February 2022) - Ou, Yunfu; Rana, Moumita; Vilatela, Juan José; González, Carlos
Abstract: Enabling energy-storing functions in structural composites is an appealing strategy to reduce the weight of systems in electric transport. Structural power composites (SPC) can be made by introducing energy-storing layers in traditional composite laminates, either as embedded devices or as thin integrated interleaves simultaneously performing load-bearing and electrochemical energy storage functions. However, the solid electrolyte in these layered architectures is typically a soft polymer, thus making the SPC very prone to delamination. Mechanical interconnection using structural matrix bridges between plies, analogous to metal connectors, provides a solution to alleviate delamination risks while maintaining the structural integrity of the SPC even under the most unfavourable combinations of loads. This paper reports on the use of experimental tests and FEM simulations to study the micromechanics of interlaminar polymer connectors in SPCs. It explores the effect of the connector area on the shear strength and energy density. The results provide a validated methodology to design laminated structural composites with a tailored balance of multi-functional properties of wide application to SPC of different constituents, with electrochemical energy storage either as capacitors or batteries. Graphical abstract: Image 1